2017
DOI: 10.4078/jrd.2017.24.4.220
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Herpes Zoster in Patients with Rheumatoid Arthritis Undergoing Biologic Disease-Modifying Therapy

Abstract: Objective. Rheumatoid arthritis (RA) patients suffer from an increased risk of herpes zoster (HZ) partially due to immunosuppressant medications. This study investigated HZ in RA patients treated with biologic disease-modifying antirheumatic drugs (bDMARDs), as compared with conventional DMARDs (cDMARDs). Methods. This retrospective case series study assembled record information of 277 RA patients who received bDMARDs after failure of at least one cDMARDs at Seoul National University Hospital between August 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In a Japanese RA cohort, crude HZ IR was 0.67 per 100 PY and risk was significantly elevated with TNFi use versus no use (odds ratio 2.28; p=0.03) but not with use of the non-TNFi bDMARDs, tocilizumab and abatacept (16). A retrospective study of patients with RA in Korea demonstrated an IR of 2.6 per 100 PY for bDMARDs overall, but found variable risk depending on the bDMARD, with higher HZ IRs for abatacept, rituximab and adalimumab (8.5, 3.9 and 3.7 per 100 PY, respectively) versus other bDMARDs (22). TNFi data demonstrated a small risk (hazard ratio 1.63) or no increased risk for TNFi overall versus csDMARD use in patients with RA or PsA (13,14), and were inconsistent regarding relative risks of specific TNFi (13,14).…”
Section: Introductionmentioning
confidence: 96%
“…In a Japanese RA cohort, crude HZ IR was 0.67 per 100 PY and risk was significantly elevated with TNFi use versus no use (odds ratio 2.28; p=0.03) but not with use of the non-TNFi bDMARDs, tocilizumab and abatacept (16). A retrospective study of patients with RA in Korea demonstrated an IR of 2.6 per 100 PY for bDMARDs overall, but found variable risk depending on the bDMARD, with higher HZ IRs for abatacept, rituximab and adalimumab (8.5, 3.9 and 3.7 per 100 PY, respectively) versus other bDMARDs (22). TNFi data demonstrated a small risk (hazard ratio 1.63) or no increased risk for TNFi overall versus csDMARD use in patients with RA or PsA (13,14), and were inconsistent regarding relative risks of specific TNFi (13,14).…”
Section: Introductionmentioning
confidence: 96%
“…In the previous issue of the Journal of Rheumatic Diseases, Kwon et al [9] reported that among the Korean RA patients, bDMARDs did not increase the risk of developing HZ compared to cDMARDs (crude incidence rate, 2.6…”
mentioning
confidence: 99%